2016
DOI: 10.1186/s12909-016-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

Transition to practice: can rural interprofessional education make a difference? A cohort study

Abstract: BackgroundThe transition from student to health practitioner at entry-to-practice is complex, requiring critical acquisition of collaborative practice skills. In rural communities where health need is multidimensional, there is potential for multiple intentional collaborative learning objectives to be met concurrently. A five-week, rurally-located, clinically-based interprofessional programme was introduced as a transition-to-practice rotation for final-year, pre-registration health professional students in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…However, a shift to VCoPs in such areas has been found to have promise to the development of vitural forms of IPE and IPC (e.g. Pullon et al, 2016). VCoPs can have a particularly positive impact on the development and support for isolated clinicians by providing them with a community to engage in, learn from and seek support from ( e.g.…”
Section: Key Issuesmentioning
confidence: 99%
“…However, a shift to VCoPs in such areas has been found to have promise to the development of vitural forms of IPE and IPC (e.g. Pullon et al, 2016). VCoPs can have a particularly positive impact on the development and support for isolated clinicians by providing them with a community to engage in, learn from and seek support from ( e.g.…”
Section: Key Issuesmentioning
confidence: 99%
“…The importance of teaching diversity and cultural competency in medical curricula is well recognised [17]. Some studies have shown that the teaching of culture and diversity can positively influence change [810], while others have not [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Students described the value of this workshop in relation to their future practice. 29 They felt that knowledge gained from the workshop has broadened their understanding of patient considerations relating to medication administration 24 , 30 and given them confidence in identifying and referring patients who may benefit from a compounded product.…”
Section: Discussionmentioning
confidence: 99%